Identifikasi Salmonella Sp Pada Terasi Yang Diperjualbelikan Di Pasar Daya Kota Makassar - Linda Linda; Abd. Gani; Isnawati Darwis (Jurnal Media Laboran, 2017)
This research has the background of typhoid fever which is a health problem for the community that occurs due to contamination of food and beverages by bacteria, germs, viruses and parasites, such as Salmonella Sp. Terasi is a spice made from shrimp or fish that is processed simply. Salmonella Sp is a microbial pathogen for humans which if ingested and enters the body can cause gatroenteritis infection which shows symptoms such as fever. This type of research is a laboratory observation with a number of shrimp paste samples of 5 samples and taken by porposive sampling with the criteria for a less clean place. This research was carried out at the Makassar Health Laboratory Center on 17 to 21 June 2014 with salmonella sp. Laboratory observation method. The results of the identification study on shrimp paste were not found to be contaminated by Salmonella Sp. This shows that the use of shrimp paste raw materials has been well processed and the equipment used is very much considered clean.